Frustration of Employees: Reasons, Dimensions and Resolving Techniques - Andalib, Tarnima Warda; Mohd Ridzuan, Darun; Azlinna, Azizan (2013)
This article ‘Employee Frustration Handling through Frustration Model’ has reflected a very insightful perception of the author as well as the facts of regular scenario of the employees’ mental state of any organization. The topic has reflected and covered the areas of the frustration of employees throughout their work lives, the reasons behind this frustration, the dimensions, the processes, development state and handling techniques of frustration. This article has revealed the pain of being frustrated and also has provided some guidelines, discussed about techniques in an individual level as well as in a social, organizational level that an organization and managers must do to prevent and handle frustration of the employees, viewing the entire issue from human rights angle. One example/case study has been described using the frustration-handling model along with describing the main concepts with examples.